Synthesis of Thymol Derivatives as Potential Non-Irritant Antimicrobial and Insecticidal Agents - El-Miligy, Mostafa M.M.; Hazzaa, Aly A.; El-Zemity, Saad R.; Al-Kubeisi, Ahmed K. (Current Bioactive Compounds, 2019)
Background: Thymol has been reported to have a variety of antimicrobial and insecticidal activities but it has irritation side effect due to its phenolic nature. Methods: A new series of potential non-irritant non-phenolic thymol derivatives were designed to hybridize the well-known biologically active thymol scaffold with various five membered heterocyclic antimicrobial and insecticidal pharmacophores like 1,3,4-oxadiazole, 1,3,4-thiadiazole, 1,2,4-triazole, thiazole and 4-thiazolidinone through different spacers. The target compounds were biologically evaluated for their in vitro antibacterial, antifungal and insecticidal activities. Results: Compounds 4b and 9c showed weak antibacterial activity against S. aureus and B.subtilis with the inhibition zone diameters ranging from 2 to 7 mm and 4 mm respectively compared with ciprofloxacin with the inhibition zone diameter of 21 mm. Compounds 9a, 7d and 13b showed weak antibacterial compounds against B. subtilis with inhibition zone diameters 4, 4 and 6 mm respectively. Compounds 12b, 9c and 7a showed 20% insecticidal activity at a concentration of 0.157 mg/cm2 for each compound against Tribolium castaneum (Herbst) and Sitophilus oryzae (L.). Compound 6 showed moderate larvicidal activity against Culex pipiens with 40% mortality at a concentration of 1000 ppm. Conclusion: Compound 9c showed weak dual antimicrobial and insecticidal activities.
Keywords: insecticide